2017
DOI: 10.1109/tuffc.2017.2703670
|View full text |Cite
|
Sign up to set email alerts
|

Total Ionizing Dose Effects on Piezoelectric Thin-Film Cantilevers With Oxide Electrodes

Abstract: This paper reports on the ionizing radiation effects in lead-zirconate-titanate (PZT) with varied top electrode material and bias condition during radiation. A technique to characterize the piezoelectric performance of films unclamped from the substrate is described, and used to demonstrate the effects of radiation on the material's electromechanical behavior. Both platinum and iridium oxide top electrodes were examined, and iridium oxide appears to significantly mitigate radiation-induced damage that is obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
1
1
Order By: Relevance
“…kV/cm at room temperature is inadequate to markedly enhance device-poling. Despite that the total dose of 1 kGy used here is well below typical literature doses 27,[29][30][31][32] and well below the radiation hardness of PZT (~50 kGy 31,32 ), the results indicate that 𝛾𝛾-radiation and bias still induce some radiationdamages even at lower exposure doses. Figure 4 (a) exemplifies typical leakage vs. time curves for eight inner, eight outer, and eight capacitors, plotted on top of each other in the same graph.…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…kV/cm at room temperature is inadequate to markedly enhance device-poling. Despite that the total dose of 1 kGy used here is well below typical literature doses 27,[29][30][31][32] and well below the radiation hardness of PZT (~50 kGy 31,32 ), the results indicate that 𝛾𝛾-radiation and bias still induce some radiationdamages even at lower exposure doses. Figure 4 (a) exemplifies typical leakage vs. time curves for eight inner, eight outer, and eight capacitors, plotted on top of each other in the same graph.…”
contrasting
confidence: 51%
“…Despite the indication of increased large-signal leakage, Figure 3 (c) and (d) shows that the permittivity and loss were not significantly affected. Zhu et al have shown that UV radiation can be used as a tool to enhance poling and also enable cold-poling 28,29 . Though 𝛾𝛾radiation and bias are expected to cause similar effects, neither the small-signal deflection nor 𝑑𝑑 𝐿𝐿𝐿𝐿 of the micromirrors increased more than the other stress tests.…”
mentioning
confidence: 99%